1995
DOI: 10.1111/j.2044-835x.1995.tb00681.x
|View full text |Cite
|
Sign up to set email alerts
|

The memory‐span deficit in children with specific reading disability: Is speech rate responsible?

Abstract: Memory span and articulation rates for one‐, two‐ and three‐syllable words were measured in three groups of 15 children: (i) children identified as having specific reading disability (SRD children), (ii) a group of chronological age‐matched (CA) controls and (iii) a group of younger normal readers matched to the SRD children for reading age (RA controls). All children had IQ scores in the normal range. The results showed that mean memory span for the SRD group was poor relative to CA controls, but approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
2
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
0
17
2
3
Order By: Relevance
“…This task, although typically used with clinical populations, is particularly appropriate for children with dyslexia, because it removes the memory component that clouds interpretation of the nonsense word and polysyllabic word repetition data. It is not clear to what extent deficits in complex tasks such as these reflect phonological components, memory demands, or some combination of the two (Nicolson et al, 1991;Nicolson and Fawcett, 1992;see Rack et al, 1992 for a review; Avons and Hanna, 1995;Edwards and Lahey, 1998;Joanisse and Seidenberg, 1998 for further links between articulation and memory). In earlier research, problems have been identified in pre-paced repetition of lengthy sequences, using a technique where errors have been specifically included (Wolff et al, 1984;Wolff et al, 1990;Snyder and Downey, 1995).…”
Section: Rapid Repetitive Articulation and Dyslexiamentioning
confidence: 97%
“…This task, although typically used with clinical populations, is particularly appropriate for children with dyslexia, because it removes the memory component that clouds interpretation of the nonsense word and polysyllabic word repetition data. It is not clear to what extent deficits in complex tasks such as these reflect phonological components, memory demands, or some combination of the two (Nicolson et al, 1991;Nicolson and Fawcett, 1992;see Rack et al, 1992 for a review; Avons and Hanna, 1995;Edwards and Lahey, 1998;Joanisse and Seidenberg, 1998 for further links between articulation and memory). In earlier research, problems have been identified in pre-paced repetition of lengthy sequences, using a technique where errors have been specifically included (Wolff et al, 1984;Wolff et al, 1990;Snyder and Downey, 1995).…”
Section: Rapid Repetitive Articulation and Dyslexiamentioning
confidence: 97%
“…Several studies reported normal word length effects in poor readers with auditory presentation (Avons & Hanna, 1995;Johnston & Anderson, 1998, Experiment 2b;McDougall & Donohoe, 2002;McDougall, Hulme, Ellis, & Monk, 1994). However, with visual presentation, inconsistent results have been reported.…”
Section: Introductionmentioning
confidence: 93%
“…This has led to debate concerning the amount of group variance attributable to deficits in phonological or memory processes (e.g., Gathercole, 1994; Gathercole, Willis, Emslie, & Baddeley, 1991; Snowling, Chiat, & Hulme, 1991). For example, it has been suggested that memory span differences between dyslexics and controls can be accounted for in terms of phonological processes, such as slow articulation rate (Avons & Hanna, 1995; Hulme, Roodenrys, Brown, & Mercer, 1995; McDougall & Donohoe, 2002) or deficits in learning, encoding, or using phonological representations (Carroll & Snowling, 2004; Kramer, Knee, & Delis, 2000; Rack, 1994; Tijms, 2004).…”
Section: Central Executive Functioning In Developmental Dyslexiamentioning
confidence: 99%
“…This has led to debate concerning the amount of group variance attributable to deficits in phonological or memory processes (e.g., Gathercole, 1994; Gathercole, Willis, Emslie, & Baddeley, 1991; Snowling, Chiat, & Hulme, 1991). For example, it has been suggested that memory span differences between dyslexics and controls can be accounted for in terms of phonological processes, such as slow articulation rate (Avons & Hanna, 1995; Hulme, Roodenrys, Brown, & Mercer, 1995; McDougall & Donohoe, 2002) or deficits in learning, encoding, or using phonological representations (Carroll & Snowling, 2004; Kramer, Knee, & Delis, 2000; Rack, 1994; Tijms, 2004).Interesting differences between dyslexics and non-dyslexics have also emerged on working memory span tasks (e.g., Ransby & Swanson, 2004; Swanson, Ashbaker, & Lee, 1996; Wolff & Lundberg, 2003). In contrast to the passive storage requirement of simple span tasks, working memory span tasks involve the simultaneous processing of information.…”
mentioning
confidence: 99%